Symbiotic Wolbachia in mosquitoes and its role in reducing the transmission of mosquito-borne diseases: updates and prospects - Minwuyelet, Awoke; Petronio, Giulio Petronio; Yewhalaw, Delenasaw; Sciarretta, Andrea; Magnifico, Irene; Nicolosi, Daria; Di Marco, Roberto; Atenafu, Getnet (Frontiers in Microbiology, 2023)
Mosquito-borne diseases such as malaria, dengue fever, West Nile virus, chikungunya, Zika fever, and filariasis have the greatest health and economic impact. These mosquito-borne diseases are a major cause of morbidity and mortality in tropical and sub-tropical areas. Due to the lack of effective vector containment strategies, the prevalence and severity of these diseases are increasing in endemic regions. Nowadays, mosquito infection by the endosymbiotic Wolbachia represents a promising new bio-control strategy. Wild-infected mosquitoes had been developing cytoplasmic incompatibility (CI), phenotypic alterations, and nutrition competition with pathogens. These reduce adult vector lifespan, interfere with reproduction, inhibit other pathogen growth in the vector, and increase insecticide susceptibility of the vector. Wild, uninfected mosquitoes can also establish stable infections through trans-infection and have the advantage of adaptability through pathogen defense, thereby selectively infecting uninfected mosquitoes and spreading to the entire population. This review aimed to evaluate the role of the Wolbachia symbiont with the mosquitoes (Aedes, Anopheles, and Culex) in reducing mosquito-borne diseases. Global databases such as PubMed, Web of Sciences, Scopus, and pro-Quest were accessed to search for potentially relevant articles. We used keywords: Wolbachia, Anopheles, Aedes, Culex, and mosquito were used alone or in combination during the literature search. Data were extracted from 56 articles' texts, figures, and tables of the included article.